Ruthenium interconnects with 58 nm2 cross-section area using a metal-spacer process - Dutta, Shibesh; Kundu, Shreya; Lianggong Wen; Jamieson, Geraldine; Croes, Kristof; Gupta, Anshul; Bommels, Jurgen; Wilson, Christopher J.; Adelmann, Christoph; Tokei, Zsolt (Proceedings of the IEEE International Interconnect Technology Conference, 2017)
Platinum-group metals have emerged as promising alternatives to replace Cu in scaled interconnects. Here, we present a short-loop test vehicle to fabricate metal nanowires with sub-100 nm 2 cross-section area without the need for multiple patterning or CMP. Ru nanowires with 58 nm 2 cross-section area, as determined by the TCR method, were realized and characterized by transmission electron microscopy and electrical measurements. The nanowires demonstrate low resistivity (27 μΩcm) and very high current carrying capacity with fusing currents as high as 720 MA/cm 2 .